COMPLICATIONS OF CLASP PROSTHETICS WITH LOCKING FASTENERS - Садриев Низом Наджмиддинович; Караев Шахбоз Фармон угли (American Journals, 2023)
The development of alternative dental services has allowed patients to choose between public dental care and private clinics. Many patients suffer from partial tooth loss at a relatively young age. Restoration of various defects with clasp and microprostheses using locking fasteners is one of the alternatives to standard treatment. At the same time, the use of fixed and removable dentures with locking fasteners of modern manufacturers require the training of doctors and dental technicians, the availability of appropriate equipment for precision casting in foundry laboratories, compliance with manufacturing technology and the correct choice of the type of locking in accordance with the characteristics of the dentition defect. The practical use of locking fasteners during dental treatment is associated with a sufficient number of complications caused by medical errors. So, in the domestic literature there is only one message about errors in dental prosthetics using lock fasteners. Particular issues related to improving the quality of the treatment and diagnostic process in orthopedic dentistry were also considered. An analysis of domestic and foreign literature shows that at present in the practice of orthopedic dentistry there is no single and formulated classification of errors and complications in dental prosthetics using locking fasteners (attachments). There is also no documentation for all stages of orthopedic treatment using this type of composite structures. In addition, as practice shows, in orthopedic dentistry with prosthetics using lock fasteners, there is a problem of conflict situations, the problem of clinical and professional assessment of medical errors and complications has not been studied, and algorithms for their solution have not been developed. Therefore, an attempt was made to study the causes of medical errors and complications in orthopedic treatment using locking fasteners in patients with partial absence of teeth and, based on the results obtained, to increase the effectiveness of orthopedic treatment. Along with this, the influence of medical and legal literacy of orthopedic dentists on the resolution of conflict situations in the provision of this type of treatment was studied.